Komparatystyka systemów politycznych na przykładzie badań aktywności parlamentów narodowych w systemie politycznym Unii Europejskiej - Borońska-Hryniewiecka, Karolina (Instytut Politologii Uniwersytetu Wrocławskiego, 2022)
This chapter is devoted to a comparative analysis of the activity of national parliaments in the political system of the European Union. Referring to the work of Andrzej Antoszewski, I discuss the specific analytical perspective, methodology and theoretical assumptions through which I sought answers to the following research questions: (1) what factors determine the activity of national parliaments in the field of European affairs; (2) to what extent do the parliamentary chambers act in these arenas as autonomous players and to what extent as actors inspired by the executive or even as agents of the government; and (3) how do the parliaments perceive themselves: do they see themselves as ‘players in multiple arenas’ oriented towards direct contact with the EU institutions or rather as national actors focused on the control of their own government? The research results indicate that important factors explaining the European activity of national parliaments are - depending on the arenas analysed - formal powers in the area of European policy, the composition of the parliamentary majority, and the parliamentary perception of the role that legislative chambers should play in the EU governance system.
Keywords: comparative politics; political system; European Union; parliaments; players in multiple arenas